Optimizing the orientation of the open spaces and building constructions for cold climate based on sunshine in borujerd city (تحقیقات کاربردی علوم جغرافیایی)
This study aimed to evaluate the climatic conditions for the establishment of Borujerd city in the design of buildings and streets of the city with an emphasis on radiant energy, an attempt to reduce problems related to cold climate is that in order to achieve this goal of data synoptic station in the city of Boroujerd a period of 23 years, including temperature, precipitation, relative humidity and other parameters as maximum, minimum and average is used. This study is cross-sectional study and extensive research studies of all documents related to the concept and the; and the method of data collection in the expression of the status quo and in Analysis of the types of library issues Bamtalh documents, and field research. The main tools of analysis in this study include Oleg bioclimatic models, Gioni and computational methods is the law of cosines In this respect, first using data from synoptic weather station borujerd in chart eco building and open spaces and drawing on its,thresholds and thermal requirements of the building inside and outside and then priorities for the design and construction of climate , urban streets is determined;The results showed that , best orientation for settlement building in Borujerd in order to optimize the energy consumption is south- north after15 west.and best orientation for streets plan in Borujerd according the  AS interaction is toward southwest- northeast and after that 60 west in order to avoid permanent ice and snow.